Structural and Dielectric Properties of Cr3+-Cu2+ Substituted Cobalt Ferrites. (May 2020) - Getso, R. S; Mohammed, J.; Tchouank Tekou Carol, T; Mukhtar, G.; Halilu, N.; Sharma, Shaweta; Srivastava, A. K.; Prasad, N.; Ahmad, M.; Basandrai, Deepak
Abstract: The current paper examined the impact of Cu 2+ -Cr 3+ substitution on the structural and dielectric possessions of nanoparticles of cobalt ferrites with the composition Co1-x Cux Fe2-x Crx O4 (x=0.0, 0.1, 0.2), synthesized via sol-gel auto-combustion technique and calcinated for 4 hours at 700°C. The XRD patterns display large peaks suggesting nanocrystalline for inverse spinel ferrite formation. FTIR indicate the formation of spinel ferrites by revealing the presence of a typical absorption band in range 390-410 cm −1 and 540-560 cm −1, respectively. FESEM reveals that the specimen is plate and sponge-like structure. In the frequency assortment 1 KHz -5 MHz, dielectric analysis at room temperature was performed and described on the foundation of the phenomenological theory of Koop and the theory of Maxwell Wagner. The result shows the highest dielectric constant without doping is 128.5. The experiment showed low dielectric loss i.e. 1.8 with x=0.2.